The Philosophical Stage : Drama and Dialectic in Classical Athens - Billings, Joshua, 1985- (Book collections on Project MUSE., 2021)
"In this book, classicist Joshua Billings considers classical Greek drama as intellectual history. Developing an innovative approach to dramatic form as a mode of philosophical thought, Billings recasts early Greek intellectual history as a conversation across types of discourses and demonstrates the significance of dramatic reflections on widely-shared conceptual questions. He integrates evidence from tragedy, comedy, and satyr play into the development of early Greek philosophy in order to place poetry at the center of Greek thought. He thus offers a substantially new history and map of classical intellectual culture: drama, on his view, appears as our best source for understanding the thought of the fifth century, while at the same time revealing significant tensions and anxieties in the development of philosophy. At the heart of the book is a novel approach to the philosophical qualities of drama. Though dramatists and their works have been considered philosophical in a variety of ways going back to antiquity, scholarly approaches have consistently taken "literature" and "philosophy" as defined categories, tracing more or less direct connections between one and the other. On the contrary, Billings argues that neither "literature" nor "philosophy" were available as stable categories in the fifth century. Rather he describes the way that drama treats issues that would come to be called philosophical, without relying on assumptions concerning what constitutes philosophical method or literary form. Drama develops a kind of method that allows it to pose and pursue conceptual questions in dramatic form which Billings describes as the "philosophical poetics" of drama"--